Ultrasound Use in Diagnosis and Management of Venous Leg Ulcer - Tanop Srisuwan (2020)
© The Author(s) 2020. Leg ulcers caused by venous diseases are effectively assessed by Doppler ultrasonography. The examination provides clear anatomical and physiological information for the diagnosis, treatment planning, and real-time guiding during the surgical treatment. Diagnostic Doppler ultrasonography assesses deep, superficial, and perforator veins, starting from patency assessment by direct visualization and simply compression test. The internal flow can be assessed by pulse wave analysis, which is used for rule out downstream flow obstruction and valvular incompetence. The venous valve function of deep, superficial, and perforator systems can be evaluated by measuring the time of the retrograde flow after flow augmentation performing in the upright position. At the end of the study, the venous map will be obtained and this map will guide clinicians to target treatment where the culprit is. The ultrasound technology has made a big shift in the treatment in the venous disease. In recent years, after the evolution and wide availability of ultrasound, newer treatment modalities have emerged for venous treatment. These include endovenous thermal ablation, endovenous adhesive closure, and ultrasound-guided foam sclerotherapy. Patients no longer require general anesthesia or hospitalization. Therefore utilization of duplex ultrasound has also surged and played an essential role in both diagnosis and therapy in venous ulcer. This article has dedicated to reviewing basic anatomy, the technique in diagnosis, and treatment.